2022
DOI: 10.1177/08850666221147229
|View full text |Cite
|
Sign up to set email alerts
|

Prone Versus Supine Ventilation and Mortality Outcome in Intubated COVID-19 Patients, a Revision Letter

Abstract: In the article, it has been mentioned that prone positioning provided a mortality benefit to intubated patients with COVID-19, as opposed to the patients who did not undergo prone positioning. It was reported that of the patients who underwent prone positioning, 77.4% died, as opposed to 83.9% of patients who did not. The authors mentioned some limitations of the study, but we think it needs to be addressed.Several factors affected the outcomes. Firstly patients' demographics were different in both groups. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…These differences could have biased the results toward prone positioning leading to a lower mortality rate. Moreover, the study did not provide details about the duration and frequency of prone positioning and whether the patients who underwent it had any adverse events or complications [ 28 ]. The study by Mathews et al showed a mortality benefit of prone positioning for patients with COVID-19 but also had some caveats.…”
Section: Reviewmentioning
confidence: 99%
“…These differences could have biased the results toward prone positioning leading to a lower mortality rate. Moreover, the study did not provide details about the duration and frequency of prone positioning and whether the patients who underwent it had any adverse events or complications [ 28 ]. The study by Mathews et al showed a mortality benefit of prone positioning for patients with COVID-19 but also had some caveats.…”
Section: Reviewmentioning
confidence: 99%